INFLECTIONAL FORMS OF TENSE AND ASPECT IN ATESO (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper is an analysis of tense and aspect in Ateso, an Eastern Niloticlanguage. Ateso distinguishes between past and non-past tenses: the pasttense is marked by a low tone on the syllable peaks of the verb, while thenon-past is marked by a high tone on the verb nucleus. With regard toaspect, it distinguishes between the following: imperfective, perfective,consecutive, perfect, habitual, and iterative. The first five aspects aremarked morphologically by the morphemes -i, -it, ko-, a- and -nenerespectively. The iterative is marked by reduplication of the verb root.Since tone, tense and aspect are assigned differently in each of the TesoTurkana subgroups, it is important that they are analysed separately for aclear view of these concepts and how they are represented specifically inAteso.